Defenisi, hakikat, pembagiaan, dan fungsi dalam bahasa - Sirait, Nurul Aulia (Maliki Interdisciplinary Journal, 2024)
This research aims to determine the definition of the nature of division and function in language. Words, Speech and Movement are one of the signs often used in language by humans as communiation between other humans. Language will become more meaningful when we use it according to the context of its use. The ontext in this language is very common where there are several definitions, the essence of which will be the background in this study uses quantitative methods by collecting data that tends to be certain. In essence, language is a sound that is spoken or spoken. What serves to express themselves language also refers to the context of society, public relations can encourage students to remain avtive in the scope of lectures, which is a benchmarkfor students in language control.